Revitalisasi Literasi Pegon di Pondok Pesantren: Studi Kasus di Pondok Pesantren Al-Huda, Bandung - Soni Sadono; Novian Denny Nugraha; Donny Trihanondo (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2026)
This study explores the revitalization of the Sundanese Pegon script through a community-based training program at Al-Huda Islamic Boarding School, Bandung. Conducted by the Community Service Team of Telkom University in June 2025, the program aimed to preserve traditional Islamic literacy by reintroducing the Pegon script to students (santri). Utilizing a qualitative-descriptive method through observation, interviews, and document analysis, the research reveals that the training successfully enhanced both the students' awareness and technical proficiency in reading and writing Pegon. Interview results with the Chairman of the Al-Huda Foundation, Roni Syahroni, emphasize that this effort is not merely an academic achievement but a vital step in reviving the historical soul of the pesantren. The findings demonstrate strong community support for preserving local cultural literacy. The study concludes that the community-based education model is highly effective and viable as a strategy to sustain the Islamic cultural heritage of Nusantara amidst modern challenges. Thus, Pegon literacy remains a spiritual and intellectual bridge for future generations.